Leprechaun in late winter - Osborne, Mary Pope (Osborne, Mary Pope. Magic tree house series., 2010)
Jack and Annie travel back to 19th-century Ireland to inspire a young Augusta Gregory to share her love of Irish legends and folktales with the world.